Dental assistants and hygienists a practical career guide - Endsley, Kezia, 1968- (Practical career guide, 2019)
Dental Assistants and Hygienists includes interviews with professionals in the field, covers three main areas of this field that have proven to be stable, lucrative, and growing professions. Dental assistants Dental hygienists Dental technicians.